Mental Health Promotions in Islamic Education: A Field Study of Faith- Based Educational Practices - Zaenal Abidin; Mustapa Ahmad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Student mental health has become a critical concern in educational systems worldwide, as rising academic pressure places students at heightened risk of stress, anxiety, and emotional fatigue. In Muslim-majority contexts, Islamic education offers a holistic framework integrating moral, spiritual, and social development; however, field-based evidence on its role in mental health promotion remains limited. This study examines how Islamic educational practices function as promotive mechanisms for student mental health and identifies contextual factors shaping their implementation. A qualitative field study was conducted in Islamic schools and pesantren in Bogor, West Java, Indonesia. Data were collected through semi-structured interviews, focus group discussions, non-participant observations, and document analysis with teachers, school leaders, and students selected through purposive sampling. Thematic analysis was employed to identify recurring patterns across the data. Findings indicate that religious routines, character education (akhlaq), and supportive teacher–student relationships serve as culturally embedded mechanisms promoting emotional regulation, meaning-making, and social connectedness. However, mental health promotion remains largely informal, constrained by limited mental health literacy, absent institutional policies, and insufficient professional support. This study highlights the need for culturally responsive, institutionally supported mental health strategies in faith-based education.